Technological development in business [electronic resource] / Video Education Australasia (Australia : Video Education Australasia, 2003)
Without adopting new technological developments, a company's profits will lag; with them, they can soar. This program uses two case studies-Ford and Australia Post-as they introduce very different types of technology in their respective organizations. Can these companies hope to maintain sales, market share, and profit if they are not in a position to exploit the latest technological advancements?